Informatics Revolution in Terms of Veterinary Medicine - Bağlıoğlu, Mehtap; Özen, Abdullah (Mersin University, 2014)
Bioinformatics is a multidisciplinary science, based on generally macromolecular level of biological information obtained knowledge conceptualized understanding of the principles for the reputation and implemention of informatics techniques. In recent decades, with the support of emerging technology in the field of bioinformatics particularly in terms of genetic notable developments have occured, these have given direction to veterinary medicine which has an important place in the field of health sciences. Cloning studies accelerated by the discovery of double helix structure of DNA, genetically modified organisms which have produced by recombinant DNA technology and a contoversial subject because of its certain disadventages, European Bovine Genom Map Project, features aimed at improving the efficiency improvements in livestock, rapid and reliable diagnostic methods, nanobiotechnology and microarray technology could be examples of progress in the field of veterinary medicine with the support of bioinformatics. These examples can advise the role of bioinformatics in terms of the veterinary medicine. In this study, it is aimed to the assessment of the developments called “informatics revolution” in terms of veterinary medicine.

Biyoinformatik; genel olarak makromoleküler düzeyde kavramsallaştırılarak elde edilen biyolojik bilginin anlaşılması ve düzenlenmesi için informatik tekniklerin uygulanması esasına dayalı multidisipliner bir bilimdir. Son onyıllarda, gelişen teknolojiden aldığı destekle biyoinformatik alanında, özellikle genetikte kayda değer gelişmeler meydana gelmiş; bunlar, sağlık bilimleri alanında önemli bir yeri olan veteriner hekimliğine yön vermiştir. DNA’nın çift sarmal yapısının keşfedilmesiyle hız kazanan klonlama çalışmaları, rekombinant DNA teknolojisi ile üretilen ve birtakım dezavantajları yüzünden tartışmalı bir konu olan genetiği değiştirilmiş organizmalar, Avrupa Sığır Genom Haritası Projesi, hayvancılıkta verim özelliklerinin iyileştirilmesine yönelik gelişmeler, hızlı ve güvenilir teşhis yöntemleri, nanobiyoteknoloji ve mikroarray teknolojisi, biyoinformatiğin desteğiyle veteriner hekimliği alanında kaydedilen gelişmelere örnek oluşturabilir. Bu örnekler, veteriner hekimliği açısından biyoinformatiğin rolüyle ilgili fikir verebilir. Bu çalışmada, “informatik devrimi” olarak adlandırılan gelişmelerin veteriner hekimliği açısından öneminin değerlendirilmesi amaçlandı.
Veteriner Hekimliği Açısından İnformatik Devrimi